Integrating Instagram Analytics into Information Systems: Enhancing Pastry Sales Through Seasonal and Non-Festive Engagement Insights - Weandri, Aliffa Ratumahesa; Wandy, Wandy; Saptaji, Kushendarsyah (Institut Teknologi Bisnis AAS Indonesia, 2025)
This study investigated the integration of Instagram analytics into the information systems used by MSMEs in the pastry industry, with a focus on engagement trends. Using a descriptive quantitative approach, the research identifies a benchmark engagement rate of 16.5%, calculated from the midpoint between peak festive engagement and regular-day averages. Findings show a sharp increase in engagement leading up to Eid, exceeding the benchmark, followed by a noticeable decline post-event. In contrast, regular day engagement remains consistently below the benchmark. These patterns highlight the impact of cultural events on consumer behavior and the difficulty of sustaining interest afterward. The study concludes that integrating social media data into enterprise systems enables MSMEs to optimize marketing strategies and time promotions more effectively and respond better to seasonal trends, offering a practical model for data-driven decision-making in small businesses.